Optimalisasi Jaringan Komputer pada Sistem Terdistribusi dalam Meningkatkan Kualitas Layanan Kesiswaan pada SMK Swasta Karya Serdang - Siahaan, R. Fanry; Gunung Juanda Tampubolon; Ayu Pelita Lumban Siantar (Jurnal Mahajana Informasi, 2023)
The need for internet in the current era has become a basic necessity in everyday life. As a private vocational school that provides vocational education, it has a responsibility to provide stable and optimal internet services to improve the quality of student services. In providing internet services, you must be able to provide stable and efficient internet services. Therefore, this research aims to evaluate and improve the quality of network services at Karya Serdang Private Vocational School through optimizing computer networks in a distributed system. This research uses mixed methods, involving literature analysis, case studies of distributed system implementation at SMK Karya Serdang, as well as data collection through interviews and surveys.